Quantitative CT detects changes in airway dimensions and air-trapping after bronchial thermoplasty for severe asthma - Konietzke, Philip; Weinheimer, Oliver; Wielpütz, Mark Oliver; Wagner, Willi Linus; Kaukel, Philine; Eberhardt, Ralf; Heußel, Claus Peter; Kauczor, Hans-Ulrich; Herth, Felix; Schuhmann, Maren (European journal of radiology, 2018)
Bronchial thermoplasty (BT) can be considered in the treatment of severe asthma to reduce airway smooth muscle mass and bronchoconstriction. We hypothesized that BT may thus have long-term effects on airway dimensions and air-trapping detectable by quantitative computed tomography (QCT).